The Difference of Celery Leaves And Bay Leaves Water to Decrease Blood Pressure among Pre-Elderly With Primary Hypertension in Public Health Center Cigugur Tengah - Tifany Desty Erisandi; Budiman (STIKep PPNI Jawa Barat, 2021)
Background: Hypertension is a medical condition in which the blood pressure in arteries is persistently elevated. This condition can increase risk of cardiovascular diseases such as stroke, kidney failure, heart attack, and kidney damage. One of traditional treatment for hypertension is using celery leaves (Apium graveolens L) and bay leaves (Syzygium polyantum). Purpose: The aimed of this research is to determine the difference of blood pressure after the consumption of celery and bay leaves water in pre-elderly with hypertension at Cigugur Tengah Public Health Center. Method: The type of this research is the numerical comparative analytic with Quasi Experiment design with Non Equivalent Control Group Design. This research used purposive sampling technique using 22 respondens with inclusion and exclusion criteria. Data collection was performed by measuring the blood pressure before and after the consumption of celery leaves and bay leaves boiled water that consume twice a day in one week. Result: The statistical result of T-independent test obtain p valueof 0,365 > α (0,05) for the systolic blood pressure and 0,574 > α (0,05) for diastolic blood pressure. The results of this study also concluded that there was an influence on blood pressure of the two intervention groups for patients with hypertension with a p value of each intervention group, a systolic p value of 0,000 and a diastolic of 0,000 with a significance level of p <α (0.05). Conclusion: Suggestion of this research is to consume boiled water of celery leaves and bay leaves for longer time as additional therapy for hypertension patient.